Cerebellar contribution to emotional body language perception: a TMS study. Issue 1 (7th October 2019) - Ferrari, Chiara; Ciricugno, Andrea; Urgesi, Cosimo; Cattaneo, Zaira
Abstract: Consistent evidence suggests that the cerebellum contributes to the processing of emotional facial expressions. However, it is not yet known whether the cerebellum is recruited when emotions are expressed by body postures or movements, or whether it is recruited differently for positive and negative emotions. In this study, we asked healthy participants to discriminate between body postures (with masked face) expressing emotions of opposite valence (happiness vs anger, Experiment 1), or of the same valence (negative: anger vs sadness; positive: happiness vs surprise, Experiment 2). While performing the task, participants received online transcranial magnetic stimulation (TMS) over a region of the posterior left cerebellum and over two control sites (early visual cortex and vertex). We found that TMS over the cerebellum affected participants' ability to discriminate emotional body postures, but only when one of the emotions was negatively valenced (i.e. anger). These findings suggest that the cerebellar region we stimulated is involved in processing the emotional content conveyed by body postures and gestures. Our findings complement prior evidence on the role of the cerebellum in emotional face processing and have important implications from a clinical perspective, where non-invasive cerebellar stimulation is a promising tool for the treatment of motor, cognitive and affective deficits.